The Feasibility Study of Reservoir Geomechanics from Brittleness Evaluation - Benyamin Elilaski Nababan; Harnanti Yogaputri Hutami; Fatkhan Fatkhan; Sonny Winardhi (Scientific Contributions Oil and Gas, 2022)
A detailed understanding regarding the rocks Brittleness Index is helpful in oil and gas exploration as upfront information to determine the rock fracture gradient. Researchers have proposed several methods to estimate the rock Brittleness Index. However, different ways may yield different results and lead to varying interpretations regarding the Brittleness Index classifi cation. This paper evaluates the Brittleness Index of an Indonesian gas well using three approaches based on the elastic properties log data, elastic properties rock physics modeling, and mineralogical rock physics modeling to assess the consistency of the methods. The results obtained in this study suggest that elastic properties-based and mineralogical methods produced a consistent Brittleness Index. However, the vertical resolution is different. It indicates that the Brittleness Index estimated from the actual log data showed higher resolution than the Brittleness Index calculated from the rock physics modeling. Combining TOC data with the Brittleness Index is recommended to optimize hydraulic fracturing design and planning. For further investigation, the authors will be suggesting direct sampling from cores and laboratory measurements to obtain the in-situ mechanical properties of shale rocks.